2006
DOI: 10.1037/h0100770
|View full text |Cite
|
Sign up to set email alerts
|

Post-trauma: Is evidence-based practice a fantasy?

Abstract: Trauma, bereavement, and loss are universal human experiences. Much has been written about the process that the bereaved go through following the loss of a loved one. Recent events such as 9/11, earthquakes in Turkey, genocides in Rwanda, community conflict in Northern Ireland, and the Asian Tsunami Disaster have drawn unprecedented public attention to the subject of traumatic bereavement. Increasingly, it is recognised that while most people are able to cope with loss generally by eventually restructuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 172 publications
(211 reference statements)
0
9
0
Order By: Relevance
“…With the beginning of the peace process, increased attention was given to victims' issues (Dillenburger et al, 2007a;Fay, Morrissey, Smyth, & Wong, 1999;Hamber, 2003;Hayes & Campbell, 2000;Kulle, 2001;Morrissey & Smyth, 2002;Northern Ireland Office, 1998;O'Reilly & Stevenson, 2003;Smyth, 1997Smyth, , 2000. After the Good Friday Agreement in 1998, victims' issues were more fully recognized (Bloomfield, 1998) and substantial support became available (Dillenburger, Akhonzada, & Fargas, 2006;McDougall, 2006): I hold the victim support group very dearly. It's like a second home to me.…”
Section: Political and Cultural Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…With the beginning of the peace process, increased attention was given to victims' issues (Dillenburger et al, 2007a;Fay, Morrissey, Smyth, & Wong, 1999;Hamber, 2003;Hayes & Campbell, 2000;Kulle, 2001;Morrissey & Smyth, 2002;Northern Ireland Office, 1998;O'Reilly & Stevenson, 2003;Smyth, 1997Smyth, , 2000. After the Good Friday Agreement in 1998, victims' issues were more fully recognized (Bloomfield, 1998) and substantial support became available (Dillenburger, Akhonzada, & Fargas, 2006;McDougall, 2006): I hold the victim support group very dearly. It's like a second home to me.…”
Section: Political and Cultural Contextmentioning
confidence: 99%
“…After the Good Friday Agreement in 1998, victims' issues were more fully recognized (Bloomfield, 1998) and substantial support became available (Dillenburger, Akhonzada, & Fargas, 2006;McDougall, 2006): I hold the victim support group very dearly. It's like a second home to me.…”
Section: Political and Cultural Contextmentioning
confidence: 99%
“…Family communication is vital and community services are used widely. However, the effectiveness of the kinds of therapeutic approaches frequently used by community groups has been called into question (Deloitte & Touche, 2001;Dillenburger, Akhonzada, & Fargas, 2006;Hamber, Kulle, & Wilson, 2001;McDougall, 2006). Data reported here suggest that even though these services are used in the long term, many of the services may not be very effective.…”
Section: Discussionmentioning
confidence: 99%
“…The mode of death or trauma plays an important role in the outcome and it is recognized that survivors of violence are at greater risk of poor bereavement outcome; the individual circumstance at the time of trauma as well as social factors play important roles in coping; and of course, cultural factors are also important (Figure 2). Clearly therefore, each person, family, and community experiences trauma and violence differently and the effects on their lives and health vary (Dillenburger et al, 2006).…”
Section: Who Needs Community Support Services?mentioning
confidence: 99%
“…There is little research on evidence of effectiveness of befriending as an intervention for traumatized individuals (Dillenburger et al, 2006). While there are no clear definitions, some research has found that befriending by volunteers (especially, if trained and supervised) may be an effective way of combating problems of loneliness and isolation (Bradshaw and Haddock, 1998;Harris et al, 1999;Heslop, 2005;Taggart et al, 2000).…”
Section: Figure 2 Risk and Protective Factors For Coping With Violencementioning
confidence: 99%